Analysis of Potential Economic Sectors on Regional Original Revenue in Gresik Regency - Alifta Salwa Amelia; Riko Setya Wijaya (Universitas Trunodjoyo Madura, 2026)
This study aims to identify potential economic sectors and analyze their influence on Regional Original Revenue (PAD) in Gresik Regency. The data used are secondary data for the 2015–2024 period obtained from the Central Statistics Agency (BPS). The analytical methods employed include Location Quotient (LQ) to determine base sectors, Shift Share analysis (PR, PS, and DS) to analyze sectoral growth and competitiveness, and multiple linear regression to examine the influence of economic sectors on PAD. The results indicate that the base sectors in Gresik Regency include Mining and Quarrying, Manufacturing Industry, Electricity and Gas Supply, and Construction. The Shift Share analysis shows that all sectors have positive Proportional Shift (PS) values; however, several sectors have negative Differential Shift (DS) values, namely Mining and Quarrying (-153.97), Electricity and Gas Supply (-4.70), and Human Health and Social Work Activities (-0.11), indicating low competitiveness in those sectors. The regression analysis results show that simultaneously the independent variables significantly influence PAD with a probability value of 0.000936. Partially, the Mining and Quarrying sector, Manufacturing Industry sector, and Construction sector significantly affect PAD, while the Electricity and Gas Supply sector does not significantly affect PAD. The Adjusted R-squared value of 0.932250 indicates that 93.22% of the variation in PAD can be explained by the variables in the model, showing a strong relationship between economic sectors and PAD.